Potential nutritive value of Trigonella spicata hay harvested at different maturity stages - Uslu, Omer Suha (Progress in Nutrition, 2021)
The aim of the current experiment  was to determine the effects of harvesting maturity on the chemical composition, dry matter digestibility (DMD), dry matter intake (DMI) and relative feed value (RFV), gas production, methane production, metabolisable energy (ME) and organic matter digestibility (OMD)  of Trigonella spicata  hay. Harvesting maturity had a significant (P